Communicative approaches to support desired organizational changes in quality of public services - Krasnykov, Yevhen (Pressing Problems of Public Administration, 2023)
The paper actualizes the issue of the use by the leaders of public organizations of communicative approaches to the implementation of organizational changes and overcoming resistance to improve the quality of public services. The aim of this paper is to investigate the development and promotion of communicative approaches to organizational changes aimed at improving the quality of public services and effectively countering resistance from public organization leaders to these changesTo enhance public service quality and overcome organizational resistance to change, altering perspectives on change is essential. This means shifting how employees view their professional environment. There’s no one-size-fits-all approach; multiple viewpoints coexist regarding understanding a changing world. This explains why some leaders prefer a rational change approach while others opt for experimentation.The article introduces a communicative approach that stresses the importance of linking internal thought processes to external actions for implementing necessary changes. Thinking skills essential for change formulation are inseparable from social skills needed for execution. Through communication, individuals can change their external environment and their own thinking. This, in turn, can impact public organizations and improve service quality.The author substantiates that the use of these methods of working with personnel allows to increase in the level of readiness of heads of public organizations at the individual and group levels, to reduce resistance, and to increase the level of efficiency of implementation of organizational changes to improve the quality of public services.